TRANSLATION AND LEXICOGRAPHIC ISSUES OF TOURISM-RELATED TERMS IN ENGLISH AND UZBEK LANGUAGES - Suvanov Ilyos Diyorovich (Modern American Journals, 2025)
This study examines the translation and lexicographic issues of tourism-related terms in English and Uzbek. It aims to identify semantic, cultural, and pragmatic challenges in translating specialized terminology and to evaluate the treatment of such terms in bilingual and explanatory dictionaries. The research applies comparative, descriptive, and analytical methods. Findings reveal that while many tourism terms are borrowed directly into Uzbek, their cultural adaptation and lexicographic representation remain inconsistent. The study suggests strategies for improving translation accuracy and dictionary standardization in the field of tourism terminology.
Keywords: Tourism terminology, translation, lexicography, English, Uzbek, semantic equivalence